Relationship Between Obesity and Asthma Control in Children Aged 4-18 years - KARADAĞ, BÜLENT TANER (SPRINGER INDIA, 2016)
Objective To analyze the relationship between obesity and asthma control in a group of patients with asthma. Methods In this prospective study, body mass index (BMI) values of 200 asthma patients aged 4-18 y who had been regularly followed up by Kartal Education and Research Hospital Pediatric Asthma Outpatient Clinic were calculated. Asthma control test (ACT) and asthma control questionnaire (ACQ) were performed. The degrees of asthma control were evaluated with regard to BMI values in consideration of the data obtained. Results The lowest and the highest BMI values were 12.4 and 30.0 kg/m(2), respectively (mean 18.1 +/- 2.9). Of the total 200 children, 110 were boys and 90 were girls. It was found that 17 % of the patients were overweight and 16 % obese. ACT results showed that 72 patients had controlled asthma, 102 patients had partially controlled asthma and 26 patients had uncontrolled asthma. According to ACQ results, 165 patients had controlled asthma, 17 patients had partially controlled asthma and 18 patients had uncontrolled asthma. Conclusions Thus, it was found that there was no statistically significant difference between asthma control degrees of obese and non-obese patients. In other words, obesity did not affect the asthma control level.
Keywords: Asthma; Obesity; Asthma control test (ACT); Asthma control questionnaire (ACQ); BODY-MASS INDEX; CHILDHOOD ASTHMA; ASSOCIATION; OVERWEIGHT; SYMPTOMS